Coordinating supply relationships: rhetoric and reality - Harrison, Alan; Koulikoff-Souviron, Marie (Cranfield University, 2007)
Two reciprocally interdependent, dyadic supply relationships – one inter- organizational, the other intra-organizational - were investigated across a broad front in this study. The focus was on the logistics relationship between supply partners, and on how these relationships were co-ordinated in practice. We probed co-ordination between the partners using four constructs – goal congruence, information sharing, co-ordination mechanisms and joint decision making. Based on these two studies, we propose that the process of mutual adjustment creates a ‘together-separate’ tension that has to be managed in practice. This process may lead to the development of new capabilities that transcend the boundaries of the firm: equally, it is a fragile process that may be thrown into reverse by a variety of factors such as people turnover and failure to maintain established coordination mec
Keywords: Supply relationships; Logistics; Coordination